DEMYSTIFYING STUDENT-UNIVERSITY IDENTIFICATION AMONG VIRTUAL TEFL CANDIDATES: THE CASE OF IRAN - Salimi, Esmaeel Ali; Banitalebi, Zahra (TEFLIN Journal, 2023)
Student-University Identification (SUI) of virtual students in higher education is one area of identity that receives less attention. This study aimed to explore the SUI of a purposive sample of five virtual students studying Teaching English as a Foreign Language (TEFL) at the Ph.D. level in Iran. Investigating SUI in higher education among virtual TEFL Ph.D. candidates potentially contributes to demystifying a complex relationship of factors, such as cultural experiences, linguistic backgrounds, and online environment challenges. Using phenomenology, the study investigated the identities of the participants by thematically analyzing semi-structured interview data. The findings revealed the participants’ various ways of identifying with a university, the subsequent consequences of identification, and the obstacles preventing them to develop SUI. The findings indicated that several factors at play are unique to doctoral candidates. The faculty prestige, research-based concerns, and nature of online media were identified to be crucial aspects of SUI for the TEFL Ph.D. students. Universities are thus advised to provide appropriate direction for virtual candidates. The study also found that some students perceived a lack of competence in TEFL, which, in turn, acted as a barrier to their SUI. To alleviate this problem, further research needs to identify what is lacking in teacher education university programs and what initiatives are required to improve TEFL students’ professional development and help them become confident English teachers.